COMPARATIVE EFFICACY OF VARIOUS DRUGS AGAINST GASTRODISCUS IN HORSES - W.A. Malik; K. Pervez; M. Avais; I. Rabbani (Journal of Animal and Plant Sciences, 2006)
This study was conducted to workout the prevalence of Gastrodiscus infection in horses in Lahore district and to check the efficacy of oxfendazole, albendazole and ivermectin against Gastrodiscus infection in horses. Five hundred faecal samples were collected and subjected to Coprological examination. From the Gastrodiscus positive horses 28 animals were selected for this study and were divided into four groups (A, B, C and D) comprising 7 animals each. The animals of group A, B, and C were treated with albendazole (Farbenda 10%; Farvet) @ 1ml/13kg bwt, oxfendazole (Oxafax; GlaxoWelcome) @ 1ml/2.2kg bwt and ivermectin (Ivomec;Rhone Poulenc) @ 1ml/50kg bwt, respectively while the animals of group D were kept as untreated control. The prevalence of Gastrodiscus infection in horses was found to be 6%. The average efficacy of oxfendazole, albendazole and ivermectin was 56.2%, 69.47% and 9.5%, respectively. Hence oxfendazole and albendazole showed better results as compare to ivermectin.
Keywords: Gastrodiscus; Oxfendazole; Albendazole; Ivermectin